An analysis of the trade balance for the main agri-food products - Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The Romanian agri-food trade has registered a permanent deficit during the last three decades (with a brief exception period, 2013-2014). The deficit was deepened by the negative trade balance with the EU countries, but since 2010, the deficit has been partially offset by the trade surplus with the non-EU countries. The paper analyzes the evolution of the agro-food trade balance detailed by the main product groups, and the results highlight the product groups that were the main contributors to the deficit and have remained over time the main import goods (fruits, meat, vegetables, milk and dairy products), those with balances shifting from negative to positive depending on the economic situation (poultry, eggs), as well as those with a permanent positive balance (cereals, oilseeds). The imports of pork, apples and tomatoes are analyzed in detail, in terms of the quantity, value and countries of origin of the imports.
Keywords: F14; Q17; 330; agri-food trade deficit; pork; apples; tomatoes